A Study of Some Community Water Supply Problems in Wilayah Persekutuan - Yaziz, Mohammad Ismail; Md Salleh, N. A. (1985)
This study was carried out to examine the various sources of water which are being used by residents in squatter settlements around Kuala Lumpur. The results showed that piped water from the public stand-pipes was used primarily Jar drinking and cooking purposes but water from other sources was also collected to augment their water supply jar use in washing, gardening, etc. An evaluation of the methods used Jar the collection and storage of water other than piped water, indicated that the system can be further improved to yield good quality water by adoption of appropriate technologies for household water treatment.